2010
DOI: 10.3109/01443610903486169
|View full text |Cite
|
Sign up to set email alerts
|

Young women opting for tubal sterilisation in rural India: Reasons and implications

Abstract: The proportion of the women using tubal sterilisation is increasing, while the age at sterilisation is dropping. This prospective cross-sectional study explores factors that influence the women in rural India to undergo tubal sterilisation at a young age. In this study, 109 married women seeking tubal sterilisation from a community health centre were interviewed. Information included baseline reproductive data, knowledge about different contraceptive methods, prior contraceptive use, and reasons for choosing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…The study highlights that lack of information and/or misinformation about temporary contraception leads to major reliance on female sterilization without thinking about its complications and future regret. 6 In addition, the vigorous promotion of female sterilization often made it the single choice of contraceptive method in women’s reproductive life. 2 The choice of sterilization is common among poor and socially disadvantaged women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study highlights that lack of information and/or misinformation about temporary contraception leads to major reliance on female sterilization without thinking about its complications and future regret. 6 In addition, the vigorous promotion of female sterilization often made it the single choice of contraceptive method in women’s reproductive life. 2 The choice of sterilization is common among poor and socially disadvantaged women.…”
Section: Discussionmentioning
confidence: 99%
“… 2 Lack of information or misinformation regarding temporary methods and less opportunity to prefer modern temporary methods due to affordability and accessibility issues also affect women’s choice of female sterilization. 6 Common misbeliefs such as “vasectomy reduces sexual desire” and “it makes a man physically weak” lead to people’s disapproval of vasectomy as a contraceptive method. 7 , 8 Even the health workers in India are not well informed about vasectomy, which makes them unable to provide appropriate information regarding vasectomy to motivate people, and therefore, they mainly provide information on female-oriented methods.…”
Section: Introductionmentioning
confidence: 99%
“…[ 3 6 ] Hormonal contraceptive usage associated with CVT was much lower (2.4%) in our study, a reflection of the preference for permanent sterilization here. [ 14 ] Improved postpartum care with a higher incidence of smoking-associated hyperhomocysteinemia in men is also the likely reason for this gender shift. [ 2 ] Headache, seizure, altered mentation, focal neurological deficit were the most commonly reported initial symptoms, similar to the existing literature.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly a prior report, in 2010, from rural part of northern India revealed that nearly half (53.2%) of the participants had never used any modern method of contraception and one third of those women had at least one prior induced abortion. [ 32 ] This reveals that in India, over a decade, there had been no change in the contraceptive behavior of the young women and women practice induced abortion for spacing birth and avoiding unwanted pregnancy. Therefore, a more focused approach with special attention to antenatal women in the antenatal clinics and indoor post-partum women may increase the contraceptive use by the eligible couples and reduce the unintended pregnancies.…”
Section: Discussionmentioning
confidence: 99%